PEMBERIAN STIKER DAN PAPAN KOMITMEN SEBAGAI UPAYA MENCIPTAKAN KAWASAN BEBAS ASAP ROKOK - Raudhotul Jannah; Deka Rahmawita; Putri Wulandari; Afrida Setia Ningsih; Novi Berliana (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2019)
Simpang Tuan Village in Tanjung Jabung Timur Distric has a fairly high smoking problem that is 79.9% (Primary Health Care Data). Based on these data, it can be concluded that smokers in Simpang Tuan village are already at the stage of addiction, as a result smoking behavior is difficult to stop. The PKM-M team has provided a method that is quite effective in dealing with people who smoke by conducting socialization activities on the dangers of smoking, giving stickers, signing petitions and making commitment boards. The purpose of this program is as a community service effort to create a smoke-free area. Methods: This program is carried out for 1 month, from April to May 2019, and ends with an evaluation of activities, namely by visiting residents' homes and asking what changes have been experienced after this program. Results: Through this program, the PKM-M team has obtained satisfactory results, because the response and appreciation of the community towards this program is very good. This can be seen from the evaluation results that show 80% of people have reduced cigarette consumption at home and people are starting to realize not to smoke in the surrounding environment. Conclusion: this method effective to reduced cigarette consumption